2019
DOI: 10.1097/rli.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Transfer Imaging Is Unaffected by Decreases in Renal Perfusion in Swine

Abstract: Objectives: Multiparametric renal magnetic resonance imaging (MRI), including diffusion-weighted imaging, magnetic resonance elastography, and magnetization transfer imaging (MTI), is valuable in the noninvasive assessment of renal fibrosis. However, hemodynamic changes in diseased kidneys may impede their ability to measure renal fibrosis. Because MTI assesses directly tissue content of macromolecules, we test the hypothesis that MTI would be insensitive to renal hemodynamic changes in swine kidneys with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
(64 reference statements)
1
16
1
Order By: Relevance
“…Therefore, a robust imaging biomarker that is less affected by confounding factors is needed for more reliable assessment of renal fibrosis. In contrast, MT‐MRI evaluates the macromolecule content, which is less affected by coexisting hemodynamic factors 7 . This supports the possible usefulness of MT‐MRI, which directly quantifies the macromolecule content, in assessing the elevated collagen deposition in renal fibrosis.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Therefore, a robust imaging biomarker that is less affected by confounding factors is needed for more reliable assessment of renal fibrosis. In contrast, MT‐MRI evaluates the macromolecule content, which is less affected by coexisting hemodynamic factors 7 . This supports the possible usefulness of MT‐MRI, which directly quantifies the macromolecule content, in assessing the elevated collagen deposition in renal fibrosis.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, a simple measurement of the MT contrast, namely, magnetization transfer ratio (MTR), reflects the macromolecular content in tissue, providing a powerful tool for assessment of renal fibrosis. Indeed, it has been previously demonstrated that MTI is insusceptible to a sudden drop in renal perfusion relative to other MRI techniques 7 . Previous studies have demonstrated the feasibility of using MTR to detect microstructural disruptions in the brain, 8 spinal cord injuries, 9 and fibrosis 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, changes in physiological conditions and hemodynamics can affect measurements on DWI and BOLD imaging, even in the absence of fibrosis. However, MT measures remain the same during functional changes in kidneys [ 137 ].…”
Section: Basic Imaging Approaches For Akimentioning
confidence: 99%
“…T2*weighed images were acquired using a multiecho gradient echo sequence with the following parameters: repetition time (TR) = 100 ms, echo time (TE) = 2.1-27 ms, Flip angle = 40°, field-of-view (FOV) = 32 cm, Slice thickness = 7 mm, and Matrix = 256 • 256. The renal hypoxia index R2* was quantified by an exponential fitting of the signal intensity and echo times [16,17], after which the renal cortical and medullary R2* values were measured [18].…”
Section: Bold Imagingmentioning
confidence: 99%